The GEMOY (GERAKAN MONITORING DEBAY): OPTIMALISASI MENINGKATKAN PENGETAHUAN IBU HAMIL TENTANG PEMANTAUAN GERAK JANIN - Rahmawati, Veronica Yeni Rahmawati; Puspasari, Jehan; Fitria, Dian (Jurnal Pengabdian Kesehatan, 2024)
Monitoring fetal movements in the womb is still not optimal for pregnant women. This is due to the lack of knowledge of pregnant women regarding ways or techniques to monitor fetal well-being which can be done at home or outside the home while working. The aim of this community service is to increase pregnant women's knowledge regarding monitoring fetal movements independently. The method used is an introduction to the stages of fetal development and health education to monitor fetal movements through fetal movement cards. Based on the results of the pretest and posttest questionnaires, it shows that there was an increase in participants' knowledge before being given education who had good knowledge by 5 people (33.3%) then after being given education participants who had good knowledge about monitoring and monitoring fetal movements increased by 13 people (88.6 %).  Providing face-to-face education and socializing the recording of fetal movement monitoring cards has been proven to increase pregnant women's knowledge in monitoring fetal movement.